2021
DOI: 10.1186/s12936-020-03545-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma angiopoietin-2 is associated with age-related deficits in cognitive sub-scales in Ugandan children following severe malaria

Abstract: Background Elevated angiopoietin-2 (Angpt-2) concentrations are associated with worse overall neurocognitive function in severe malaria survivors, but the specific domains affected have not been elucidated. Methods Ugandan children with severe malaria underwent neurocognitive evaluation a week after hospital discharge and at 6, 12 and 24 months follow-up. The relationship between Angpt-2 concentrations and age-adjusted, cognitive sub-scale z-scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Irrespective of infection etiology, plasma Angpt-2 levels were elevated in severe AKI. These results are consistent with Angpt-2 as a marker of disease severity in critical illness [4,[25][26][27]30,[34][35][36]. Angpt-2 levels have been implicated in both severe malaria and sepsis-associated AKI [30,37].…”
Section: Discussionsupporting
confidence: 83%
“…Irrespective of infection etiology, plasma Angpt-2 levels were elevated in severe AKI. These results are consistent with Angpt-2 as a marker of disease severity in critical illness [4,[25][26][27]30,[34][35][36]. Angpt-2 levels have been implicated in both severe malaria and sepsis-associated AKI [30,37].…”
Section: Discussionsupporting
confidence: 83%
“…Among children up to five years old, a greater risk for the development of impairment in motor skills, receptive and expressive language, visual reception and social interaction has been identified ( Brim et al., 2017 ; Ouma et al., 2021 ). Multiple seizures, prolonged coma and intracranial hypertension during CM appear to be related to the risk of neurological sequelae including epilepsy ( Idro et al., 2004 ; Idro et al., 2006 ; Kariuki et al., 2011 ).…”
Section: Neurocognitive and Behavioral Sequelae Of Severe Malariamentioning
confidence: 99%
“…Although this study focused specifically on CSF markers, previous studies from the larger cohort have shown widespread endothelial activation associated with AKI. Specifically, increases in Angiopoietin-2, associated with increased vascular permeability and AKI, was associated with increased BBB dysfunction and worse cognitive outcomes across the age spectrum ( Ouma et al, 2020 , 2021 ). Increased BBB dysfunction associated with increased systemic endothelial activation is a likely mechanism by which uremic solutes and other host and parasite proteins cross the BBB leading to oxidative stress, inflammation, and brain injury.…”
Section: Discussionmentioning
confidence: 99%